2006
DOI: 10.1099/vir.0.81435-0
|View full text |Cite
|
Sign up to set email alerts
|

Identification and genome characterization of Heliothis armigera cypovirus types 5 and 14 and Heliothis assulta cypovirus type 14

Abstract: Genomic characterization of Heliothis armigera cypovirus (HaCPV) isolated from China showed that insects were co-infected with several cypoviruses (CPVs). One of the CPVs (HaCPV-5) could be separated from the others by changing the rearing conditions of the Heliothis armigera larvae. This finding was further confirmed by nucleotide sequencing analysis. Genomic sequences of segments S10-S7 from HaCPV-14, S10 and S7 from HaCPV-5, and S10 from Heliothis assulta CPV-14 were compared. Results from database searches… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…However, whether these few sequences with homology to Nora virus are indicative of a novel and infective virus would require additional experiments. Apart from the unigenes with homology to ssRNA viruses mentioned above, we have also found sequences with high homology to the Heliothis armigera cytoplasmic polyhedrovirus 5 (HaCPV5) (Li et al, 2006b). Cytoplasmic polyhedroviruses, also known as cypoviruses (family Reoviridae), have their genome (dsRNA) fragmented into 10 segments that encode structural and non-structural viral proteins.…”
Section: Viral Sequences In the S Exigua Transcriptomementioning
confidence: 96%
“…However, whether these few sequences with homology to Nora virus are indicative of a novel and infective virus would require additional experiments. Apart from the unigenes with homology to ssRNA viruses mentioned above, we have also found sequences with high homology to the Heliothis armigera cytoplasmic polyhedrovirus 5 (HaCPV5) (Li et al, 2006b). Cytoplasmic polyhedroviruses, also known as cypoviruses (family Reoviridae), have their genome (dsRNA) fragmented into 10 segments that encode structural and non-structural viral proteins.…”
Section: Viral Sequences In the S Exigua Transcriptomementioning
confidence: 96%
“…The type 5 Helicoverpa armigera cypovirus (HaCPV-5) was initially isolated by our laboratory in 2006 from a mixture of HaCPVs and can quickly cause lethal disease in H. armigera, which is one of the most serious agricultural pests in China (24). Thus far, the RNA genome of HaCPV-5 has been completely sequenced (24,25).…”
Section: Introductionmentioning
confidence: 99%
“…The type 5 Helicoverpa armigera cypovirus (HaCPV-5) was initially isolated by our laboratory in 2006 from a mixture of HaCPVs and can quickly cause lethal disease in H. armigera, which is one of the most serious agricultural pests in China (24). Thus far, the RNA genome of HaCPV-5 has been completely sequenced (24,25). HaCPV-5 RNA segment 8 contains a single open reading frame that encodes a 44-kDa protein, and further sequence and structural analysis using bioinformatic tools has revealed that this 44-kDa protein is the VP5 capsid protein (11,12,26).…”
Section: Introductionmentioning
confidence: 99%
“…Most CPV infections produce chronic disease with low mortality, although some are pathogenic (Mertens et al , 1999, 2004). Helicoverpa armigera Cytoplasmic polyhedrosis virus (HaCPV) (Chinese strain) is a mixture of CPV, so that Belloncik et al (1996) using cell culture, separated type 14., Li et al (2006) separated type 5 from a mixture of HaCPVs. They reported that HaCPV is virulent to H. armigera and has the potential to be used as a bioinsecticide.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, alternative control measures, such as biological control agents, are required. HaCPV is a highly infectious insect pathogen (Li et al, 2006; Martignoni and Iwai, 1981) and a candidate for biocontrol of H. armigera , especially in combination with B. thuringiensis toxins (Iwashita, 1971; Kawase and Miyajima, 1971; Katagiri et al , 1978; Ying, 1986). Presently there is no description of the histopathology of HaCPV on cotton bollworm, H. armigera .…”
Section: Introductionmentioning
confidence: 99%